2008
DOI: 10.1016/j.jada.2008.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Poverty-Related Factors Associated with Obesity Prevention Policies in Utah Secondary Schools

Abstract: To address the childhood obesity epidemic, numerous national agencies have outlined specific school policy recommendations for nutrition and physical activity. The extent to which current policies differ by socioeconomic status and geographic location is yet to be determined. This cross-sectional study examined select school nutrition and physical activity policies by markers for poverty among 209 middle and high schools in Utah (82% response rate). The results show that students’ opportunities to establish he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 16 publications
0
35
2
Order By: Relevance
“…Unlike previous studies, 24,25 the current study found, on average, no policy differences by FRPL eligibility or minority enrollment. In our sample of schools, it was difficult to separate the influence of race/ethnicity, socioeconomic status, and location in shaping policy environments, given that few Minnesota town or rural schools have a high minority enrollment, and few schools with high FRPL eligibility have low minority enrollment.…”
Section: Resultscontrasting
confidence: 94%
See 2 more Smart Citations
“…Unlike previous studies, 24,25 the current study found, on average, no policy differences by FRPL eligibility or minority enrollment. In our sample of schools, it was difficult to separate the influence of race/ethnicity, socioeconomic status, and location in shaping policy environments, given that few Minnesota town or rural schools have a high minority enrollment, and few schools with high FRPL eligibility have low minority enrollment.…”
Section: Resultscontrasting
confidence: 94%
“…At least two other (cross-sectional) studies of secondary schools – one in Utah and one in a multistate sample of secondary schools – found that rural schools trailed behind city schools in a number of policies and practices to promote healthy eating. 24,25 Rural schools may be particularly understaffed, overwhelmed by academic achievement tests, or lack wellness coordinators to implement policy. 14 Although these challenges may not be unique to rural schools, they may contribute to the lack of prioritizing initiatives aimed at improving nutrition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, other studies have shown that school-based overweight/obesity prevention programs have not altered school nutrition and physical activity (25, 134, 143145), specifically if applied in rural areas with lower SES (145). A comprehensive review article associates these negative findings, at least in part, with the lack of assessment of eating disorders and other psychiatric disorders in most of these studies, and with inadequacy of the measurements used to assess change in overall well-being, functioning, and other relevant psychological variables (146).…”
Section: Intervention Programsmentioning
confidence: 95%
“…Often, limited household budgets force parents and caregivers to choose less healthy, more energy-dense foods, thereby perpetuating the likelihood for weight gain and other weight-related problems (Inglis, Ball, & Crawford, 2005). In addition, Nanney, Bohner, and Friedrichs (2008) reported that the majority of schools that offered free or reduced-price lunches were more likely to offer unhealthy food and snack options to students than schools that did not offer such options. Clearly, all of these factors combine to worsen the rising problem of obesity in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%